Analisis Pemilihan Gaya Bahasa Dalam Iklan Sosial Media Instagram di Era Pandemi Covid-19 - Syakir Haziq, Juan; Juliana, Juliana; Handayani, Nur (PT. Alahyan Publisher Sukabumi, 2025)
The COVID-19 pandemic has major implications in the context of language use in society. This study aims to analyze stylistic features in the context of COVID-19-related social advertisements that appear on social media, in particular, prevention messages and health protocols that are emphasized. This research uses a descriptive qualitative method with data collection techniques through observation and documentation. Data were analyzed using qualitative data analysis as stated by Miles and Huberman. The findings of this study reveal that the most used language features in the TV program are hyperbole and anaphora, followed by personification, pleonasm, litotes, climax, and assonance. The strength of this slogan lies in the use of these language features in a social advertisement geared towards complying with COVID-19 health protocols. This research is expected to respond to social issues by anticipating the social consequences of language used in health campaigns during the pandemic context.